VÍA, ITER, ACTUS Y LIMES: CONTRIBUCIÓN DE LA TERMINOLOGÍA DE LA JURISPRUDENCIA CLÁSICA AL ESTUDIO DE LA ORGANIZACIÓN DEL ESPACIO RURAL ROMANO EN A CUENCA ALTA DEL SEGURA (MURCIA) - López Campuzano, Manuel (Antigüedad y Cristianismo, 2019)
This paper intends to show the importance of some comcepts coming from the terminology of the Roman Classic Jurisprudence for the study of the organization of the Roman rural landscape. Concretely this exposition in concerned with part of the road plan belonging to the Cuenca Alta del Segura (Cieza-Calasparra) and its hierarchy in relation with some concepts (via, iter, actus and limes) originating in the Roman rural servitude. For this purpose it’s also necessary to analyse archaeologically the roman settlements in the area under study.